TEXT CRITERIA AND TEXT TYPES TO IMPROVE STUDENTS’ READING LITERACY - Shakhlo Naralieva; Normuminova Dilobar (Galaxy International Interdisciplinary Research Journal, 2024)
This small study examines the theoretical and practical aspects of reading literacy. The foreign material was studied and experiments were conducted on it. In the experience, it became clear that the importance of the text in improving the reading literacy of the students, and the purposeful assignments are important. In the article, the criteria for writing texts to improve their literacy and the reading skills of students who worked on creating different texts will be raised to a higher level, what types of texts should be downloaded for test tasks, the criteria that should be followed when completing the text and the principles are explained.